Binge Alcohol Consumption in Emerging Adults: Anterior Cingulate Cortical "Thinness" Is Associated with Alcohol Use Patterns. (24th June 2014) - Mashhoon, Yasmin; Czerkawski, Charles; Crowley, David J.; Cohen‐Gilbert, Julia E.; Sneider, Jennifer T.; Silveri, Marisa M.
<x xml:space="preserve">Abstract</x> Background The brain undergoes dynamic and requisite changes into the early 20s that are associated with improved cognitive efficiency, particularly in prefrontal regions that are still undergoing neuromaturation. As alcohol consumption is typically initiated and progresses to binge drinking (BD) during this time, the objective of the present study was to investigate the impact of binge alcohol consumption on frontal lobe cortical thickness in emerging adults. Methods Twenty‐three binge drinking (11 females, mean age 22.0 ± 1.2) and 31 light drinking (15 females, mean age 21.5 ± 1.6) emerging adults underwent high‐resolution magnetic resonance imaging at 3 Tesla. Cortical surface reconstruction and thickness estimation were performed using FreeSurfer for 3 a priori brain regions of interest: bilateral anterior cingulate cortex (ACC), posterior cingulate cortex (PCC), and parieto‐occipital sulcus (POS). Cortical thickness measurements were then compared between binge drinker (BD) and light drinker (LD) groups. Results Cortical thickness was significantly lower in BD than LD in the right middle ACC (mid‐ACC; p ≤ 0.05) and in the left dorsal PCC (dPCC; p ≤ 0.01). No significant differences in cortical thickness were observed in the POS. Cortical thickness in the mid‐ACC correlated negatively with higher quantity and frequency of drinks consumed (p < 0.01) and positively with the number of days elapsed since most recent use (p < 0.05). Furthermore, less cortical thickness in the mid‐ACC in the BD group alone correlated with reported patterns of high quantity and frequency of alcohol consumption (p ≤ 0.05). Conclusions Findings suggest that past and recent patterns of intermittent heavy alcohol consumption are associated with less frontal cortical thickness (i.e., "thinness") of the right mid‐ACC and left dPCC in emerging adults, but not the POS. While cortical thinness could have predated binge drinking, this pattern of maladaptive consumption may have acute neurotoxic effects that interfere with the finalization of neuromaturational processes in the vulnerable frontal cortex, resulting in increased microarchitectural pruning.